Imlifidase Inhibits HLA Antibody-mediated NK Cell Activation and Antibody-dependent Cell-mediated Cytotoxicity (ADCC) In Vitro. Issue 8 (August 2020) - Ge, Shili; Chu, Maggie; Choi, Jua; Louie, Sabrina; Vo, Ashley; Jordan, Stanley C.; Toyoda, Mieko
Abstract : Background: Antibody-dependent cell-mediated cytotoxicity (ADCC) is an important pathway responsible for antibody-mediated rejection (AMR). Imlifidase (IdeS) cleaves human IgG into F(ab')2 and Fc fragments, potentially inhibiting ADCC. Here we examined the effect of IdeS on allo-antibody-mediated NK cell activation (Allo-CFC) and ADCC in vitro. Methods: For Allo-CFC, normal whole blood was incubated with third-party peripheral blood mononuclear cells (PBMCs) pretreated with anti-HLA antibody positive (HS) or negative (NC) sera to measure IFNγ+ NK cell%. For ADCC, normal PBMCs were incubated with Farage B (FB) cells with HS or NC sera to measure 7-AAD+ lysed FB cell%. To assess the effect of IdeS on these assays, serum-treated PBMCs (Allo-CFC-1) and serum used for PBMC pretreatment (Allo-CFC-2) in Allo-CFC, and serum used for ADCC were preincubated with IdeS. Sera from IdeS-treated patients were also tested for Allo-CFC (Allo-CFC-3). Results: IFNγ+ NK cell% were significantly elevated in HS versus NC sera in Allo-CFC-1 (10 ± 3% versus 2 ± 1%, P = 0.001), Allo-CFC-2 (20 ± 10% versus 4 ± 2%, P = 0.01) and 7AAD+ FB cell% (11 ± 3% versus 4 ± 2%, P = 0.02) in ADCC. These were significantly reduced by IdeS treatment. Patient sera with significantly reduced anti-HLA antibody levels at 1 day postimlifidase lost the capacity to activate NK cells in Allo-CFC-3, but those at 1–3 months postimlifidase regained the capacity. Conclusions: IdeS inhibited NK cell activation and ADCC in vitro and in treated patients. These results and reported inhibition of complement activating anti-HLA antibodies by IdeS suggest its possible role in treatment of AMR. Abstract : Supplemental Digital Content is available in the text.